Análise computacional de pórticos planos protendidos - Mendes, Joao Amilton (1988)
The present work is concerned with the analysis of prestressed plane frames, assuming as essential parameters the frame geometry, the concrete strenght, the effort envelope, the mecanic and geometric properties of prestressed cables and the tensile force at active anchorages. The generated code all ows the plane frames analysis considering fixed and pinned supports and also free supports which show movements at the direction parallel to one of the cartesian axes. Frames with members incline in relation to the axes may also be analised when they do not have cables in the inclined members. The tendon must be placed in members which are paralel to one of the cartesian axes . It is also directioned, to continuun beams which are particular cases of frame structures, when all beams are in the same direction. In this development, structural matrix analysis techniques based on displacement process were adopted. Numerical algorithms were developed and transformed into computer codes to be used in IBM-PC type micro-computers with 256 Kb central memory. Fortran-77 is the computer language used. After running the computer code all efforts due to the prestressing are obtained: bending moments, normal and shear forces for all cross section under analysis. With the prestressing responses, efforts due to the dead load and the envelops of total actions, the normal stresses on the pre-compressed and opposite edges are computed for every section. Finally, three examples on the application of the computer code are shown: a two-pinned rectangular frame, a simply supported beam and a three- span rectangular frame.